A Rare Case Report of Intrathyroidal and Subcutaneous Bronchogenic Cyst, the Hidden Pearls in Unusual Sites - B. Vinothkumar; T. Mitila; Sridevi; Sonti Sulochana (Dr. Annil Mahajan, 2023)
Bronchogenic cyst is a rare congenital anomaly arising from the ventral bud of the foregut or tracheobronchial tree. It most commonly presents in the mediastinum, with rare ectopic presentation, accounting for 10% to 15% of mediastinal tumors and 50 to 60% of all mediastinal cysts. In this article, we discuss cases of intrathyroidal bronchogenic cyst and subcutaneous bronchogenic cyst.